Eksklusivisme Al-Quran: Reinterpretasi Konsep Menundukkan Pandangan Bagi Laki-Laki Mukmin Perspektif Betrand Russell - Rinaldo Rinaldo; Yosi Vanesa Aulia (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2022)
Abstract In this modern era, the interaction between men and women in the real and virtual worlds can no longer be limited, while the literal-textual meaning of the Qur'an implies to lower or hold one's gaze to the opposite sex. This kind of problem is not in line with the dictum of the Koran as a blessing for the whole world, because there is a debate in the world of language in the Koran with the world of reality in social society in terms of lowering the view. The author uses the logical atomic theory initiated by Betrand Russel with a descriptive-analytical-critical presentation model that adheres to a deconstruction work system to answer the question of how the Koran responds to the issue of looking down for Muslim men in the current modernization era, and what is the form of reinterpretation of Qs. . An-Nur: 30 in the concept of subduing the views of Muslim men using the semiotic perspective of Betrand Russell. So that the results of the research are in the form of a new interpretation of the meaning of Surah An-Nur: 30, among which, first, the context of Surah An-Nur: 30 discusses the consequences of the views that have been carried out, not about the law. Second, this view is a necessity, only needs to be adjusted to the situation and conditions to achieve benefit. Third, the new interpretation of An-Nur: 30 is in accordance with Indonesian culture and customs in accordance with religious norms and cultural norms. Keywords : Exclusiveism, Reinterpretation, Betrand Russell